Potentially Pathogenic Multidrug-Resistant Escherichia coli in Lamb Meat - Gozi, Katia Suemi; Deus Ajude, Luana Perpetua Tobias; Barroso, Marlon do Valle; Silva, Caroline Rodrigues da; Peiro, Juliana Regina [UNESP]; Mendes, Luiz Claudio Nogueira [UNESP]; Nogueira, Mara Correa Lelles; Casella, Tiago (Mary Ann Liebert, Inc, 2021)
Extended-spectrum cephalosporin (ESC) resistance remains a threat since ESC are important antimicrobials used to treat infections in humans and animals. Escherichia coli is an important source of ESC-resistance genes, such as those encoding extended-spectrum beta-lactamases (ESBLs). E. coli is a common commensal of lambs. Reports that contaminated food can be a source of ESC-resistant bacteria in humans and that ESBL-producing E. coli are found in sheep in Brazil led us to survey their presence in retail lamb meat. Twenty-five samples intended for human consumption were screened for ESC-resistant E. coli, and the isolates were characterized. IncI1-bla(CTX-M-8) and IncHI2-bla(CTX-M-2) were the main plasmids responsible for ESC resistance. The plasmids harbored common ESBL genes in Enterobacteriaceae from food-producing animals in Brazil. IncI1-bla(CTX-M-14) and IncF-bla(CTX-M-55) plasmids, associated with human infections, were also detected. Few CTX-M-producing E. coli have been clustered by typing methods, and some may be genetically pathogenic. The findings indicate the presence of diverse strains of E. coli, harboring important ESBL genes, in lamb meat in Brazil. Surveillance of ESC-resistant bacteria could reduce the spread of antimicrobial resistance through the food chain.
Keywords: antimicrobial resistance; CTX-M; Enterobacteriaceae; food-production chain; Brazil